Online self-learning - Ádámkó, Éva (International Journal of Engineering and Management Sciences, 2020)
In this paper four short sessions are reviewed in the theme of introductory programming. The sessions were performed in four different student groups from the age twelve to seventeen in two different schools. The paper summarizes important input and output properties of the groups, like the preliminary studies of Informatics and the grades in both Informatics and Mathematics – if available – also the results of the learning process during the sessions. The focus is on the skills of programming and self-learning, and the differences of it in respect to the age, the gender and the preliminary studies.